Best practices for television journalists a handbook for reporters, producers, videographers, news directors and other broadcast professionals on how to be fair to the public - Westin, Av 1929-; Freedom Forum (Arlington, VA Freedom Forum, 2000)
A handbook of best practices for television and broadcast journalists, encouraging practices that the public will see as being fair, thereby helping assure that television news gathering remains free.
"For the Freedom Forum's Free Press/Fair Press Project."
Cover title.
Keywords: Television broadcasting of news -- Handbooks, manuals, etc; Broadcast journalism -- Handbooks, manuals, etc; Journalistic ethics -- Handbooks, manuals, etc